Analysis of Civil Apparatus Management in East Bolaang Mongondow Regency - Yocom, Jonna Fiona; Sendouw, Recky; Bulo, Laurens (Abdurrauf Science and Society, 2025)
This study aims to determine, analyze and describe the Civil Servant Transfer Process between Organizational Units in One Agency Held in East Bolaang Mongondow Regency and its determinant factors. The research method used in this study is a descriptive qualitative research method. The focus of this study is the transfer of Civil Servants between work units. The research informants consist of structural officials in BKPSDM, functional officials, and transferred Civil Servants. The results of this study indicate that there are five indicators and determinant factors in the implementation of Civil Servant Transfers between OPDs, namely: (1) transfer requirements that have not been implemented optimally, (2) transfer procedures that have not been implemented optimally, (3) transfer provisions that have not been fully fulfilled, (4) OPD of origin and initial/recipient OPD that have not been implemented optimally, (5) PPK Decisions on Transfers which become the decision of the transferred Civil Servants, and the determinant factor is the leadership's discretion. Although some Civil Servant Transfers between regional apparatus organizations have followed BKN Regulation No. 5 In 2019, there were still civil servant transfers that were not in accordance with the merit system due to closeness to the leadership or incompatibility of work competencies.